Anthropogenic global shifts in biospheric N and P concentrations and ratios and their impacts on biodiversity, ecosystem productivity, food security, and human health - Penuelas, Josep; Janssens, Ivan A; Ciais, Philippe; Obersteiner, Michael; Sardans, Jordi (Global change biology, 2020)
The availability of carbon (C) from high levels of atmospheric carbon dioxide (CO2 ) and anthropogenic release of nitrogen (N) is increasing, but these increases are not paralleled by increases in levels of phosphorus (P). The current unstoppable changes in the stoichiometries of C and N relative to P have no historical precedent. We describe changes in P and N fluxes over the last five decades that have led to asymmetrical increases in P and N inputs to the biosphere. We identified widespread and rapid changes in N:P ratios in air, soil, water, and organisms and important consequences to the structure, function, and biodiversity of ecosystems. A mass-balance approach found that the combined limited availability of P and N was likely to reduce C storage by natural ecosystems during the remainder of the 21st Century, and projected crop yields of the Millennium Ecosystem Assessment indicated an increase in nutrient deficiency in developing regions if access to P fertilizer is limited. Imbalances of the N:P ratio would likely negatively affect human health, food security, and global economic and geopolitical stability, with feedbacks and synergistic effects on drivers of global environmental change, such as increasing levels of CO2 , climatic warming, and increasing pollution. We summarize potential solutions for avoiding the negative impacts of global imbalances of N:P ratios on the environment, biodiversity, climate change, food security, and human health.
Keywords: water; ecosystem productivity; human health; biospheric N and P concentrations; soil and plant N:P ratios; biodiversity; anthropogenic global shifts; food security